Electoral politics in Punjab factors and phases - Kumar, Ashutosh 1963- (Routledge, 2020)
"This book examines electoral politics in the state of Punjab, India as it has evolved since the colonial period. It underlines the emergence of the state as a singular unit for electoral analysis in the last three decades. This book: Charts the common trends and developments that have dominated politics in Punjab, and those that continue to play an important role in the government of the state; Examines state parties and their leadership in the context of party alliances, campaigns and electoral verdicts; Presents a comparative study of the assembly and Lok Sabha elections held in the state after reorganisation in 1966 with the objective of highlighting differences in electoral issues taken up by the parties. An important intervention in the study of state-level politics in India, this book will be of great interest to students and researchers of politics, especially comparative politics and political institutions, political sociology and social anthropology, and South Asian studies"--